The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.5501/wjv.v4.i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Current molecular methods for the detection of hepatitis C virus in high risk group population: A systematic review

Abstract: Hepatitis C virus (HCV) is an emerging infection worldwide and the numbers of persons infected are increasing every year. Poor blood transfusion methods along with unsafe injection practices are potential sources for the rapid spread of infection. Early detection of HCV is the need of the hour especially in high risk group population as these individuals are severely immunocompromised. Enzyme Immunoassays are the most common detection techniques but they provide no evidence of active viremia or identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…In the last decade, technologies to assess HCV Ab and RNA levels and our knowledge to use this information to treat HCV infection has improved significantly. 22 Additionally, DAAs have helped achieve >95% cure rates (defined as SVR at 12 weeks) for HCV infection. 11,13 Schlendorf et al 11 reported their single center experience of 11 adult HTs using HCV-viremic donor hearts.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, technologies to assess HCV Ab and RNA levels and our knowledge to use this information to treat HCV infection has improved significantly. 22 Additionally, DAAs have helped achieve >95% cure rates (defined as SVR at 12 weeks) for HCV infection. 11,13 Schlendorf et al 11 reported their single center experience of 11 adult HTs using HCV-viremic donor hearts.…”
Section: Discussionmentioning
confidence: 99%
“…However, other than the 5 0 UTR region, the core region is also targeted for PCR based detection of HCV, as a recent study has shown that sequence divergence of the core region is greater than the divergence of the 5 0 UTR sequence. Hence, detection based on the sequence of the core region can reliably identify subtypes as well as major genotypes [13].…”
Section: Detection Of Hepatitis C Virus Ribonucleic Acidmentioning
confidence: 99%
“…Sofosbuvir, a newer antiviral drug has altered the situation with regard to HCV cures by pegylated/ standard interferon and ribavarin which previously achieved in some 23%-90% individuals. [11][12][13][14][15][16][17][18] Nowadays, not only sofosbuvir but also other newer oral antiviral agents are associated with complete cure rates of around 99%-100% with or without interferon. [19][20][21][22][23] The ELECTRON trial has shown 100% SVR with dual interferon-free regime containing sofosbuvir and ribavirin in genotypes 2 and 3.…”
Section: Discussionmentioning
confidence: 99%